Florida Dairy Farm Situation and Outlook 2007 - Russ Giesy; Albert De Vries (EDIS)
AN180, a 4-page report by Russ Giesy and Albert De Vries, is one of a series of annually published reports on the dairy industry in Florida, based on the results of a survey by the Dairy Business Analysis Program (DBAP). It includes discussion of the situation and outlook, as well as background information on the challenges facing the dairy industry in Florida: production, economic, environmental, and social.  Published by the UF Department of Animal Sciences, February 2007.